2013
DOI: 10.2478/s11686-013-0171-5
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii, Neospora caninum and tick-transmitted bacterium Anaplasma phagocytophilum infections in one selected goat farm in Slovakia

Abstract: Parasitic diseases of livestock together with poor welfare conditions can negatively affect the health status and production of small ruminants. Protozoan parasites and tick-borne infectious agents are common threat of livestock including small ruminants mostly during the pasture season. Therefore the priority of the study was to analyse the circulation and presence of two protozoan parasites Toxoplasma gondii and Neospora caninum as well as tick-transmitted bacterium Anaplasma phagocytophilum in one selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 42 publications
2
9
0
Order By: Relevance
“…This suggests that climatic and management factors facilitate the survival of oocysts in the environment and the contact between definitive and intermediate hosts. The high seroprevalence values of T. gondii found in this present study also implies a real risk for public health [4].The higher individual prevalence observed for T. gondii than for N. caninum in Galician caprine livestock is in agreement with several European serological studies in goats where both protozoans were investigated [16,17,18,19]. These studies show T. gondii individual seroprevalences greater than 53%, whereas N. caninum values do not exceed 16%.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This suggests that climatic and management factors facilitate the survival of oocysts in the environment and the contact between definitive and intermediate hosts. The high seroprevalence values of T. gondii found in this present study also implies a real risk for public health [4].The higher individual prevalence observed for T. gondii than for N. caninum in Galician caprine livestock is in agreement with several European serological studies in goats where both protozoans were investigated [16,17,18,19]. These studies show T. gondii individual seroprevalences greater than 53%, whereas N. caninum values do not exceed 16%.…”
Section: Discussionsupporting
confidence: 91%
“…This may be the reason for identification of T. gondii seropositivity as a risk factor for N. caninum seropositivity and vice versa. In contrast, Čobádiová et al [17] observed a better specificity of the cELISA-VMRD using the manufacturer's cut-off value.…”
Section: Discussionmentioning
confidence: 85%
“…Similar to a previous study [ 37 ], 22.89% (76/332) of goats were positive for A. phagocytophilum infection followed by A. bovis (62/332, 18.67%) and A. ovis (43/332, 12.95%), which was not consistent with other reports indicating that the prevalence of A. phagocytophilum in goats was lower than that of A. bovis and A. ovis [ 18 ]. In addition, the prevalence of A. phagocytophilum in goats in this study was higher than that of goats in Slovakia [ 8 ]. Unlike a previous report [ 18 ], the dominant co-infection of A. phagocytophilum + A. bovis (34/332, 10.24%) was higher than A. phagocytophilum + A. ovis (22/332, 6.63%) and A. bovis + A. ovis (16/332, 4.82%).…”
Section: Resultsmentioning
confidence: 95%
“…Co-infection by T. gondii and Anaplasma has been reported in rodents [ 27 ], dogs [ 10 ], ticks [ 35 ], and wild boars [ 22 ]. However, a survey on the occurrence of goats co-infected by T. gondii and Anaplasma was only reported in Slovakia [ 8 ]. In this study, 43 out of 332 (12.95%) goats were positive for T. gondii and Anaplasma ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation